(3aJM GdbOjQ GdLGeY Hjf afj GdQhGjI hGdOQGjI ef Yde GdJaSjQ (B/s - (3GdThcGfj, eMeO Hf Ydj Hf eMeOs 1173-1250 (3gLQjs; (3YejQI, YHO GdQMefs; (3OGQ GdhaGA ddWHGYI hGdfTQ hGdJhRjY (B((3GdefUhQI (B- (3eUQ(B).s (3dLfI GdJMbjb hGdHMK GdYdej (B.s ((3GdefUhQI (B- (3LeghQjI eUQ GdYQHjI (B:s (3OGQ GdhaGA ddWHGYI hGdfTQ hGdJhRjY ,s, 2005)
(3jYJHQ cJGH aJM GdbOjQ ddEeGe GdThcGfj CUdG ef CUhd GdJaSjQ, heQLYG ef Cge eQGLYg, dCfg LeY Hjf GdJaSjQ HGdQhGjI hGdJaSjQ HGdOQGjI, MjK CLGO ajg eDdag aj HGH GdQhGjI, hJhSY aj HGH GdOQGjI, aLeY Hjf GdJaSjQ HGdQCj hGdJaSjQ HGdeCKhQ, dPdc CWdb Ydjg GSe (B: (3aJM GdbOjQ GdLGeY Hjf afj GdQhGjI hGdOQGjI ef Yde GdJaSjQ(B.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B.s
Keywords: (3GdbQBfs -- (3JaGSjQ SfjIs